Preclinical Characterization of the Selective JAK1 Inhibitor LW402 for Treatment of Rheumatoid Arthritis - Zhang N; Zhang C; Zeng Z; Zhang J; Du S; Bao C; Wang Z (Dove Medical Press, 2021)
Ning Zhang,1 Changqing Zhang,2 Zhihong Zeng,1 Jiyong Zhang,1 Shengnan Du,1 Chunde Bao,3 Zhe Wang1 1Longwood Biopharmaceuticals, Shanghai, People’s Republic of China; 2Department of Orthopaedics, Shanghai Sixth People’s Hospital, Shanghai, People’s Republic of China; 3Department of Rheumatology, Ren Ji Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of ChinaCorrespondence: Zhe Wang Email zhe.wang@lwbiopharma.comBackground: Research on JAK family members as therapeutic targets for autoimmune diseases has brought tofacitinib and baricitinib into clinical for the treatment of rheumatoid arthritis and other autoimmune diseases. Despite the potent efficacy of these first-generation JAK inhibitors, their broad-spectrum JAK inhibition and adverse events warrant development of a JAK1-specific inhibitor to improve their safety profile.Methods: In this study, we characterized a JAK1-specific inhibitor, LW402, on biochemical and human whole-blood assays. We further evaluated the therapeutic efficacy of LW402 in a rat adjuvant-induced arthritis (rAIA) model and a mouse collagen-induced arthritis (mCIA) model. The safety of LW402 was evaluated in both SpragueDawley rats and cynomolgus monkeys.Results: LW402 exhibited potent nanomolar activity against JAK1 and showed a 45-fold selectivity for inhibition of JAK1- over JAK2-dependent signaling induced by either IL6 or GM-CSF in human whole-blood assays. In the rAIA model, oral dosing of LW402 resulted in a dose-dependent improvement in disease symptoms, including reduction in paw swelling, marked reduction in the inflammatory-cell infiltration to synovial tissue, and protection of articular cartilage and bone from damage. The therapeutic efficacy of LW402 correlated well with the plasma exposure of LW402 and the extent of pSTAT3 inhibition in white blood cells. LW402 also effectively eased disease symptoms in the mCIA model. Toxicity studies in the Sprague Dawley rats and cynomolgus monkeys established a ≥ 5x therapeutic window for LW402 as drug exposures of toxicity study NOAEL dose and pharmacology study ED50 dose were compared.Conclusion: We developed a novel JAK1-specific inhibitor LW402 with potent efficacy in rAIA and mCIA models. We established a good safety profile for LW402 in toxicity studies, and the overall superiority of LW402 should translated well to the clinical setting for the treatment of RA and other autoimmune diseases.Keywords: rheumatoid arthritis, JAK1 inhibitor, rat-AIA model, mouse CIA